Reconceptualizing Legal Protection Against Deepfake Technology: A Normative Analysis of Privacy, Personality Rights, and Digital Evidence - Azka Syifaul Maula; Ali Hardana (Lex Recta: Journal of Law and Normative Justice, 2026)
The rapid development of deepfake technology has generated significant challenges for contemporary legal systems by destabilizing traditional conceptions of privacy, personal identity, and evidentiary authenticity. This study aims to reconceptualize legal protection against deepfake technology through a normative and doctrinal analysis of privacy rights, personality rights, and digital evidence. Employing a non-empirical legal research methodology, the study examines international human rights instruments, statutory regulations, judicial developments, legal doctrines, and comparative regulatory approaches concerning artificial intelligence and synthetic media governance. The analysis demonstrates that existing legal frameworks remain fragmented because privacy regulations primarily focus on informational control, personality-rights doctrines have not fully adapted to synthetic identity replication, and evidentiary regimes continue to rely upon assumptions of authenticity that are increasingly vulnerable to algorithmic manipulation. Deepfake technology creates a multidimensional legal injury that simultaneously affects identity integrity, individual autonomy, dignity, and procedural justice. The study argues that effective legal protection requires an integrated normative framework that recognizes synthetic identity harms as violations of interconnected legal interests. Such a framework strengthens legal certainty, enhances rights protection, and supports the development of more reliable evidentiary standards in digitally mediated societies.